Comparison of artesunate–mefloquine and artemether–lumefantrine fixed-dose combinations for treatment of uncomplicated Plasmodium falciparum malaria in children younger than 5 years in sub-Saharan Africa: a randomised, multicentre, phase 4 trial. Issue 10 (October 2016) - Sirima, Sodiomon B; Ogutu, Bernhards; Lusingu, John P A; Mtoro, Ali; Mrango, Zakayo; Ouedraogo, Alphonse; Yaro, Jean Baptiste; Onyango, Kevin Omondi; Gesase, Samwel; Mnkande, Ernest; Ngocho, James Samwel; Ackermann, Isabelle; et al.
Summary: Background: WHO recommends combinations of an artemisinin derivative plus an antimalarial drug of longer half-life as treatment options for uncomplicated Plasmodium falciparum infection. In Africa, artemether–lumefantrine is the most widely used artemisinin-based combination therapy, whereas artesunate–mefloquine is used infrequently because of a perceived poor tolerance to mefloquine. WHO recommends reconsideration of the use of artesunate–mefloquine in Africa. We compared the efficacy and safety of fixed-dose artesunate–mefloquine with that of artemether–lumefantrine for treatment of children younger than 5 years with uncomplicated P falciparum malaria. Methods: We did this multicentre, phase 4, open-label, non-inferiority trial in Burkina Faso, Kenya, and Tanzania. Children aged 6–59 months with uncomplicated malaria were randomly assigned (1:1), via a computer-generated randomisation list, to receive 3 days' treatment with either one or two artesunate–mefloquine tablets (25 mg artesunate and 55 mg mefloquine) once a day or one or two artemether–lumefantrine tablets (20 mg artemether and 120 mg lumefantrine) twice a day. Parasitological assessments were done independently by two microscopists who were blinded to treatment allocation. The primary outcome was the PCR-corrected rate of adequate clinical and parasitological response (ACPR) at day 63 in the per-protocol population. Non-inferiority was shown if the lower limit of the 95% CI for the difference between groups was greater than −5%. Early vomiting was monitored and neuropsychiatric status assessed regularly during follow-up. This study is registered with ISRCTN, number ISRCTN17472707, and the Pan African Clinical Trials Registry, number PACTR201202000278282. Findings: 945 children were enrolled and randomised, 473 to artesunate–mefloquine and 472 to artemether–lumefantrine. The per-protocol population consisted of 407 children in each group. The PCR-corrected ACPR rate at day 63 was 90·9% (370 patients) in the artesunate–mefloquine group and 89·7% (365 patients) in the artemether–lumefantrine group (treatment difference 1·23%, 95% CI −2·84% to 5·29%). At 72 h after the start of treatment, no child had detectable parasitaemia and less than 6% had fever, with a similar number in each group (21 in the artesunate–mefloquine group vs 24 in the artemether–lumefantrine group). The safety profiles of artesunate–mefloquine and artemether–lumefantrine were similar, with low rates of early vomiting (71 [15·3%] of 463 patients in the artesunate–mefloquine group vs 79 [16·8%] of 471 patients in the artemether–lumefantrine group in any of the three dosing days), few neurological adverse events (ten [2·1%] of 468 vs five [1·1%] of 465), and no detectable psychiatric adverse events. Interpretation: Artesunate–mefloquine is effective and safe, and an important treatment option, for children younger than 5 years with uncomplicated P falciparum malaria in Africa. Funding: Agence Française de Développement, France; Department for International Development, UK; Dutch Ministry of Foreign Affairs, Netherlands; European and Developing Countries Clinical Trials Partnership; Fondation Arpe, Switzerland; Médecins Sans Frontières; Swiss Agency for Development and Cooperation, Switzerland.